Improved Multibody Dynamics for Investigating Energy Dissipation in Train Collisions Based on Scaling Laws - Heng Shao; Ping Xu; Shuguang Yao; Yong Peng; Rui Li; Shizhong Zhao (Shock and Vibration)
This study aimed to investigate energy dissipation in train collisions. A 1/8 scaled train model, about one-dimensional in longitudinal direction, was used to carry out a scaled train collision test. Corresponding multibody dynamic simulations were conducted using traditional and improved method model (IMM) in ADAMS. In IMM, the connection between two adjacent cars was expressed by a nonlinear spring and energy absorbing structures were equivalently represented by separate forces, instead of one force. IMM was able to simulate the motion of each car and displayed the deformation of structures at both ends of the cars. IMM showed larger deformations and energy absorption of structures in moving cars than those in stationary cars. Moreover, the asymmetry in deformation proportion in main energy absorbing structures decreased with increasing collision speed. The asymmetry decreased from 11.69% to 3.60% when the collision speed increased from 10 km/h to 36 km/h.